Valsartan-mediated chronotherapy in spontaneously hypertensive rats via targeting clock gene expression in vascular smooth muscle cells. (4th March 2022) - Luan, Jiajie; Yang, Kui; Ding, Yanyun; Zhang, Xiaotong; Wang, Yaqin; Cui, Haiju; Zhou, Deixi; Chen, Lu; Ma, Zhangqing; Wang, Wusan; Zhang, Wen; Liu, Xiaoyun
Abstract: Objective: This study was to investigate the underlying mechanisms of valsartan chronotherapy in regulating blood pressure variability. Methods: RT-PCR was used to assay clock genes expression rhythm in the hypothalamus, aortic vessels, and target organs after valsartan chronotherapy. WB was used to measure Period 1 (Per1), Period 2 (Per2) protein expression in aortic vessels, as well as to measure phosphorylation of 20-kDa regulatory myosin light chain (MLC20 ) in VSMCs. Results: Specific clock genes in the hypothalamus, and Per1 and Per2 in aorta abdominalis, exhibited disordered circadian expression in vivo . Valsartan asleep time administration (VSA) restored circadian clock gene expression in a tissue- and gene-specific manner. In vitro, VSA was more efficient in blocking angiotensin II relative to VWA, which led to differential circadian rhythms of Per1 and Per2, ultimately corrected MLC20 phosphorylation. Conclusion: VSA may be efficacious in regulating circadian clock genes rhythm, then concomitantly correct circadian blood pressure rhythms.